The role of external auditor in the adoptionof computer-assisted audit techniques with unified theory of acceptance and use of technology: An empirical study in public audit firms in Jakarta - Deniswara, Kevin; Henky, Thomas; Mulyawan, Archie Nathanael; Armand, Wishnu Kameshwara; Mustapha, Mazlina (Universitas Bina Nusantara, 2023)
This research aimed to analyze the factors that influence the acceptance of Computer Assisted Audit Techniques (CAATs) among external auditors in Public Audit Firms in Jakarta. The Unified Theory of Acceptance and Use of Technology (UTAUT) approach was used for this analysis. Technological advancements had an effect on auditors' ability to adopt audit software. However, it had been found that there was no preparation or openness from auditors, leading to suboptimal utilization of audit implementation software and affected the presentation of audit information. This investigation adopted a quantitative method by distributing close-ended questionnaires to external auditors in audit firms in Jakarta. The data were analyzed using Partial Least Square with SmartPLS Ver 3. The results showed that social influence affected behavioral intention of external auditors in Jakarta in adopting and using CAATs. Expectancy performance, effort expectancy, and facilitating conditions did not affect behavioral intention of external auditors in adopting and using CAATs. This research generated contributions that could be further directed toward the development of auditor